Family morph matters: factors determining survival and recruitment in a long‐lived polymorphic raptor. (27th April 2016) - Sumasgutner, Petra; Tate, Gareth J.; Koeslag, Ann; Amar, Arjun
Summary: From an evolutionary perspective, recruitment into the breeding population represents one of the most important life‐history stages and ultimately determines the effective population size. In order to contribute to the next generation, offspring must survive to sexual maturity, secure a territory and find a mate. In this study, we explore factors influencing both offspring survival and their subsequent recruitment into the local breeding population in a long‐lived urban raptor, the black sparrowhawk ( Accipiter melanoleucus ). Adult black sparrowhawks show discrete colour polymorphism (dark and light morphs), and in South Africa, morphs are distributed clinally with the highest proportion of dark morphs (c.75%) present in our study population on the Cape Peninsula. Parental morph was associated with both survival and recruitment. For survival, parental morph combination was important – with young produced by pairs of contrasting morphs having higher survival rates than young fledged from like‐pairs. The association between recruitment and morph was more complex; with an interaction between male morph and breeding time, whereby recruitment of offspring from dark morph fathers was more likely when fledging earlier in the season. The opposite relationship was found for light morph fathers, with their offspring more likely to be recruited if fledged later in the season. This interaction may be due to differential morph‐specific hunting success of fathers (males contribute most food provisioning), linked to background matching and crypsis in different weather conditions. Dark morph males may hunt more successfully in rainier and cloudier conditions, which occur more frequently earlier in the breeding season, and light morph males may be more successful later on, when weather conditions become increasingly brighter and drier. Our results reveal a complex situation whereby the family morph combination influences survival, and the father morphs specifically recruitment, revealing morph‐specific benefits dependent on the timing of breeding. These empirical data are among the first to support the idea that differential fitness consequence of morph combination may explain balanced polymorphism in a vertebrate population. Abstract : The authors study contributes new findings to two important topics in animal research: the maintenance of colour polymorphism and urban ecology. The authors use long‐term data of urban black sparrowhawks to explore how the colour morphs of the parents (in isolation and in combination) influence key demographic parameters: offspring survival and recruitment.